2021
DOI: 10.1177/23743735211008310
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Care Experience of Patients Diagnosed With COVID-19

Abstract: Virtual models of care are seen as a sustainable solution to the growing demand for health care. This paper analyses the experience of virtual care among patients diagnosed with COVID-19 in home isolation or health hotel quarantine using a patient-reported experience questionnaire. Results found that patients respond well to virtual models of care during a pandemic. Lessons learned can inform future developments of virtual care models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 8 publications
1
43
0
Order By: Relevance
“…One such intervention is the RPA Virtual Hospital (rpavirtual), launched in February 2020 as a new model of care that combines integrated hospital and community care with digital solutions. It was the first service to introduce virtual care for COVID-19-stable patients in isolation in New South Wales, Australia, and has been demonstrated to be widely accepted by patients [ 29 ]. However, the potential equity issues related to rpavirtual and other similar virtual care interventions have not yet been adequately explored and described.…”
Section: Introductionmentioning
confidence: 99%
“…One such intervention is the RPA Virtual Hospital (rpavirtual), launched in February 2020 as a new model of care that combines integrated hospital and community care with digital solutions. It was the first service to introduce virtual care for COVID-19-stable patients in isolation in New South Wales, Australia, and has been demonstrated to be widely accepted by patients [ 29 ]. However, the potential equity issues related to rpavirtual and other similar virtual care interventions have not yet been adequately explored and described.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID‐19 pandemic radically transformed health care delivery, with massive increases in telehealth and remote services (Jonnagaddala et al, 2021 ; Raffan et al, 2021 ; Slomski, 2020 ). Early reports suggested that blood‐oxygen saturation was an important, but silent, clinical warning sign of deterioration among COVID‐19 patients (Shah et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our health service of four hospitals and five community centres, a virtual care service for remote patient monitoring was launched in 2020 to provide additional pathway of care between primary care providers, individuals, and tertiary centres, where this model provides an opportunity to improve patient centred care. The virtual care service caters for (a) people in the community who are immune‐suppressed; (b) mental health patients; (c) patients of the fracture clinic; and (d) COVID‐19 patients in home isolation 17,18 . Almost 4000 people were cared for in the first year of its launch with patients reporting a high degree of satisfaction, particularly in relation to being monitored virtually, increased confidence in their own care, and improved access to specialist services 19…”
Section: Introductionmentioning
confidence: 99%
“…The virtual care service caters for (a) people in the community who are immune-suppressed; (b) mental health patients; (c) patients of the fracture clinic; and (d) COVID-19 patients in home isolation. 17,18 Almost 4000 people were cared for in the first year of its launch with patients reporting a high degree of satisfaction, particularly in relation to being monitored virtually, increased confidence in their own care, and improved access to specialist services. 19 Our previous study, 20 conducted in one health service in Australia, tested the acceptability and effectiveness of the Tissue Analytics™ digital wound application (digital app) 21 among clinicians.…”
mentioning
confidence: 99%